Risk, incidence and predictors of venous thromboembolism among patients attending the emergency department of tertiary care hospitals in Addis Ababa city, Ethiopia: a multicentre prospective study - Desalew Mekonnen; Alemseged Beyene Berha; Worku Degefa; Minyahil Alebachew Woldu (BMJ Open)
Objective This study aimed to assess the risk, incidence and predictors of venous thromboembolism (VTE) among patients admitted to the emergency department of tertiary hospitals in Addis Ababa city, Ethiopia.Design A multicentre hospital-based prospective follow-up study was conducted.Setting The study was conducted in three tertiary care hospitals in Addis Ababa city, Ethiopia: Tikur Anbesa Specialized Hospital, Addis Ababa Burn Emergency and Trauma Hospital and St. Paulos Hospital Millennium Medical College.Participants A total of 422 patients admitted to the adult emergency wards of the selected hospitals during the study period were included.Main outcome measures The study assessed the level of VTE risk, incidence and independent risk factors for VTE.Results Nearly half (51.7%) of the study participants were male, with a mean age of 49.36 (±17.12) years. Around one-third of patients (130, 30.8%) were unable to perform physical activity, and about two-thirds had comorbid illnesses. The most common admission diagnosis was trauma (23.7%), followed by infectious disease (19.2%). More than two-thirds (70.64%) of patients were at high risk of developing VTE according to the Padua Risk Prediction Score. Eighteen patients (4.3%) were diagnosed with VTE during their emergency stay. Multivariate Cox regression analysis revealed that patients who were physically active prior to admission (adjusted hazard ratio (AHR)=0.67, 95% CI 0.082 to 1.579, p=0.014) and those receiving pharmacological prophylaxis (AHR=0.167, 95% CI 0.037 to 0.768, p=0.021) were found to have a protective effect against the risk of developing VTE. Conversely, patients with acute infection (AHR=8.169, 95% CI 1.045 to 63.854, p=0.045) and active cancer (AHR=5.133, 95% CI 1.241 to 21.093, p=0.023) had a higher risk of VTE incidence.Conclusion The study found that the risk and incidence of VTE were high among patients in the emergency department. Absence of pharmacological prophylaxis, physical inactivity prior to admission, active cancer and acute infection were identified as independent predictors of VTE incidence during emergency ward stays.